THE INFLUENCES OF CHITOSAN FROM Penaeus monodon ON C-REACTIVE PROTEIN EXPRESSION IN AORTA AND CORONARY ARTERY OF SPRAGUE DAWLEY RATS BY HIGH FAT INDUCTION - Sri Isdadiyanto; Sukarti Moeljopawiro; Nyoman Puniawati; Hastari Wuryastuty (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The objective of this study was to analyze the influences of chitosan on C-Reactive Protein expression in aorta and coronary artery of Sprague Dawley rats by high fat induction. The animals for this study were 20 adult male rats divided into four groups, i.e. group I as the control was fed with basal diet containing normal fat for 3 months, group II was fed diet containing high fat for 3 months, group III was fed diet containing high fat and given chitosan 180 mg per kg body weight per day orally in  2 ml aquadest for 3 months, group IV was fed diet containing high fat for 3 months and  after 1 month given chitosan 180 mg per kg body weight per day orally in 2 ml aquadest for 2 months. Each group consisted of five animals. After 90 days, the rats were necropsied and the hearts were collected to histopathological and immunohistochemical analysis by immunohistochemistry streptavidin-biotin method. C-Reactive Protein expression in aorta was negative. Chitosan was able to prevent atheroma plaque formation in coronary artery and CRP may involve in atherosclerosis.